FAKTOR FAKTOR PENGHAMBAT KESEJAHTERAAN PETANI SAWAH DI DESA TOMOK KECAMATAN SIMANINDO KABUPATEN SAMOSIR - Ester H Sitindaon; Randa Putra Kasea Sinaga (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The purpose of this study is to identify the factors that hinder the welfare of farmers in Tomok Village, Simanindo District, Samosir Regency. The population in this study consists of rice farmers. The sampling method used was simple random sampling, involving three (3) rice farmers as respondents, along with several external sources relevant to the study. The data obtained were analyzed using a qualitative descriptive approach. The inhibiting factors affecting the welfare of rice farmers in Sangia Makmur Village include the number of family members, land area, and capital loans, which were found to have a significant correlation with welfare levels. Based on the discussion of the relationship between these inhibiting factors and the welfare of rice farmers in Tomok Village, it can be concluded that the welfare level of rice farmers in this village can be categorized as being at the poverty line. However, several farmers still face challenges such as a high number of dependents, limited land area, and outstanding capital loans. The relationship between the inhibiting factors and the welfare of rice farmers in Tomok Village indicates that internal factors—such as the number of family dependents, education level, productive age, and selling value of harvests—affect the farmers’ welfare. Similarly, external factors such as agricultural extension assistance (PPL) and support from the village head also influence the advocacy and implementation of agricultural practices in Tomok Village.